Synthesis of a novel category of pseudo-peptides using an Ugi three-component reaction of levulinic acid as bifunctional substrate, amines, and amino acid-based isocyanides - Khalesi, Maryam; Ziyaei Halimehjani, Azim; Martens, Jürgen (Beilstein Journal of Organic Chemistry, 2019)
The synthesis of a novel category of pseudo-peptides via intramolecular Ugi reaction of levulinic acid (4-oxopentanoic acid), aromatic and aliphatic amines, and amino acid-based isocyanides is reported. Levulinic acid was applied as a bifunctional substrate containing both carbonyl and acid moieties suitable for the Ugi reaction. This article provides a facile and convenient one-pot procedure for the synthesis of peptide-like heterocyclic molecules containing 2-pyrrolidone (γ-lactam), amide and ester functional groups with good to excellent yields.
Keywords: amino acid-based isocyanides; levulinic acid; multicomponent; pseudo-peptides; Ugi reaction

(untitled) - Dömling, A. (Chem. Rev., 2006)

(untitled) - Touré, B. B.; Hall, D. G. (Chem. Rev., 2009)

(untitled) - Sunderhaus, J. D.; Martin, S. F. (Chem. – Eur. J., 2009)

(untitled) - Wang, H.-Y.; Shi, D.-Q. (ACS Comb. Sci., 2013)

(untitled) - Xiao, Z.; Lei, M.; Hu, L. (Tetrahedron Lett., 2011)

(untitled) - Abonia, R.; Castillo, J.; Insuasty, B.; Quiroga, J.; Nogueras, M.; Cobo, J. (ACS Comb. Sci., 2013)

(untitled) - Fu, L.-P.; Shi, Q.-Q.; Shi, Y.; Jiang, B.; Tu, S.-J. (ACS Comb. Sci., 2013)

(untitled) - Wang, S.-L.; Cheng, C.; Wu, F.-Y.; Jiang, B.; Shi, F.; Tu, S.-J.; Rajale, T.; Li, G. (Tetrahedron, 2011)

(untitled) - Vilches-Herrera, M.; Knepper, I.; de Souza, N.; Villinger, A.; Sosnovskikh, V. Y.; Iaroshenko, V. O. (ACS Comb. Sci., 2012)

(untitled) - Rajesh, S. M.; Bala, B. D.; Perumal, S.; Menéndez, J. C. (Green Chem., 2011)

Pseudo-peptides in Drug Discovery - Nielsen, P. E. (Wiley-VCH, 2004)

(untitled) - Ugi, I.; Steinbrückner, C. (Angew. Chem., 1960)

(untitled) - Xu, Z.; Ayaz, M.; Cappelli, A. A.; Hulme, C. (ACS Comb. Sci., 2012)

(untitled) - Gunawan, S.; Hulme, C. (Org. Biomol. Chem., 2013)

(untitled) - Rhoden, C. R. B.; Rivera, D. G.; Kreye, O.; Bauer, A. K.; Westermann, B.; Wessjohann, L. A. (J. Comb. Chem., 2009)

(untitled) - Foley, C.; Shaw, A.; Hulme, C. (Org. Lett., 2016)

(untitled) - Koopmanschap, G.; Ruijter, E.; Orru, R. V. (Beilstein J. Org. Chem., 2014)

(untitled) - Morone, A.; Apte, M.; Pandey, R. A. (Renewable Sustainable Energy Rev., 2015)

Cereals - Ghorpade, V.; Hanna, M. (Industrial Applications for Levulinic Acid, 1997)

(untitled) - Ugi, I.; Steinbrückner, C. (Chem. Ber., 1961)

(untitled) - Obrecht, R.; Toure, S.; Ugi, I. (Heterocycles, 1984)

(untitled) - Kehagia, K.; Ugi, I. K. (Tetrahedron, 1995)

(untitled) - Nitta, H.; Hatanaka, M.; Ishimaru, T. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Hanusch-Kompa, C.; Ugi, I. (Tetrahedron Lett., 1998)

(untitled) - Mironov, M. A.; Ivantsova, M. N.; Mokrushin, V. S. (Mol. Diversity, 2003)

(untitled) - Lambruschini, C.; Basso, A.; Moni, L.; Pinna, A.; Riva, R.; Banfi, L. (Eur. J. Org. Chem., 2018)

(untitled) - Ziyaei Halimehjani, A.; Sharifi, M. (Tetrahedron, 2017)

(untitled) - Ziyaei Halimehjani, A.; Ranjbari, M. A.; Pasha Zanussi, H. (RSC Adv., 2013)

(untitled) - Khalesi, M.; Halimehjani, A. Z.; Franz, M.; Schmidtmann, M.; Martens, J. (Amino Acids, 2019)

(untitled) - Patil, P.; Kurpiewska, K.; Kalinowska-Tłuścik, J.; Dömling, A. (ACS Comb. Sci., 2017)

(untitled) - Liu, H.; Dömling, A. (J. Org. Chem., 2009)